2013
DOI: 10.5194/hess-17-1913-2013
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of numerical weather prediction model precipitation forecasts for short-term streamflow forecasting purpose

Abstract: Abstract. The quality of precipitation forecasts from four Numerical Weather Prediction (NWP) models is evaluated over the Ovens catchment in Southeast Australia. Precipitation forecasts are compared with observed precipitation at point and catchment scales and at different temporal resolutions. The four models evaluated are the Australian Community Climate Earth-System Simulator (ACCESS) including ACCESS-G with a 80 km resolution, ACCESS-R 37.5 km, ACCESS-A 12 km, and ACCESS-VT 5 km.The skill of the NWP preci… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
94
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(99 citation statements)
references
References 42 publications
5
94
0
Order By: Relevance
“…Similarly, the lead time of weather forecasts could vary from time to time and sometimes the shorter the better [42]. In many instances, forecasting the start of rainfall can be significantly seasonal with some intervals of months as the expected lead time [43]. Sometimes, weather forecasts often come with associated implications for agricultural production in terms of plant and livestock pathogen development and expected incidence of some diseases.…”
Section: Access and Sources Of Weather Forecastsmentioning
confidence: 99%
“…Similarly, the lead time of weather forecasts could vary from time to time and sometimes the shorter the better [42]. In many instances, forecasting the start of rainfall can be significantly seasonal with some intervals of months as the expected lead time [43]. Sometimes, weather forecasts often come with associated implications for agricultural production in terms of plant and livestock pathogen development and expected incidence of some diseases.…”
Section: Access and Sources Of Weather Forecastsmentioning
confidence: 99%
“…As underlined by (Shrestha et al, 2013) the evaluation of NWP model output for streamflow forecasting purposes should be done with a hydrological perspective, and we thus wish to do the same for urban drainage flow forecasting. Hence as suggested by (Pappenberger et al, 2008), we based the forecast evaluation on a coupled meteorological and hydrological model, using discharge predictions and discharge observations (rather than precipitation forecasts and observations).…”
Section: Material: Nwp Data and Hydrological Modelmentioning
confidence: 99%
“…Liguori et al (2012) merged radar extrapolation data and highresolution NWP forecast data for urban runoff flow prediction purposes (6 hours lead time) and concluded that the overall performance of their rainfall forecasting system decreased with increasing rainfall intensities. NWPs have also been used for forecasting/prediction in other fields: from frost prediction used for optimising road salting and prediction of power production from wind and solar energy (Bacher et al, 2009;Giebel et al, 2005) to streamflow forecasting (Cuo et al 2011;Shrestha et al 2013), reservoir inflow prediction (Collischonn et al, 2007) and flood forecasting (Damrath et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Shrestha et al (2013)). The first 1095 pairs (three years of data) of forecast-observation are sampled from the original forecast-observation pairs, with replacement and verification scores calculated.…”
Section: Statistical Treatment Of Forecasts 20mentioning
confidence: 99%